2021
DOI: 10.1111/iju.14600
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the prenatal environment on cryptorchidism: A narrative review

Abstract: Cryptorchidism, the absence of testes from the scrotum, is the most common genital disorder in boys and a risk factor for reduced fertility and testicular cancer. The mechanism responsible for cryptorchidism involves two discrete stages: a transabdominal and an inguinoscrotal phase. These phases of testicular descent are regulated by the prenatal sex hormone environment, including levels of testosterone, insulin-like factor 3, and calcitonin gene-related peptide. Environmental endocrine disruptors, which are u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 76 publications
(89 reference statements)
0
7
0
Order By: Relevance
“…Cryptorchidism is a common condition in boys. [14] The testes may continue to descend till six months of age after which the chances of spontaneous descent are very low. Children with undescended testis at six months of age should be operated before a year of age.…”
Section: Discussionmentioning
confidence: 99%
“…Cryptorchidism is a common condition in boys. [14] The testes may continue to descend till six months of age after which the chances of spontaneous descent are very low. Children with undescended testis at six months of age should be operated before a year of age.…”
Section: Discussionmentioning
confidence: 99%
“…After that period, the possibility of spontaneous testicular descent is extremely low. Recent recommendations suggest that optimal timing for orchiopexy, to avoid infertility and testicular cancer is between 6 and 18 months of age [1][2][3][4][5]26]. Although there are many controversies regarding hormonal therapy in boys with non-palpable cryptorchidism, a recent systematic review and meta-analysis showed that hormonal therapy can be effective in some cases and increase the success rate of complete testicular descent [27].…”
Section: Discussionmentioning
confidence: 99%
“…Undescended testes (UDT) or cryptorchidism is one of the most common surgical disorders of the inguino-scrotal region in children and is one of the common causes of male infertility [1]. Recent studies have demonstrated that about 10% of infertile men have a history of UDT and orchiopexy [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations